Analisis Kekuatan Pelat Lantai Dermaga di Pelabuhan Ciwandan Banten Terhadap Penambahan BMC - Nusa Setiani; Galih Pribadi; Achmad Romadonsyah (Fakultas Teknik Universitas Krisnadwipayana, 2022)
Pier 005B is located at Pelabuhan Indonesia II (Persero) Branch of Banten and has a length of 300meters and a width of 44 meters. It is planned that at Pier 005B, will be putted 1 (one) unit of Harbor MobileCrane (HMC) brand LHM 420 will be placed as a supporting tool for loading and unloading activities from andto ships. This HMC certainly has certain specifications and capacities, so it must be calculated properly againstthe additional load that can be accepted by the floor slab of Pier 005B. The research method used is descriptivequalitative. This HMC is capable of carrying a maximum load of 124 tons at a distance of 12 to 16 meters. Withthe HMC's own weight of 371 tons and the assumption of a human weight of 0.4 tons/meter2, the total weight ofHMC received by the floor slab is 22.68 tons/meter2. By using the SAP 2000 version 22 computer application,the ultimate internal forces due to the load on the floor slab are the ultimate moment of 7.27 ton.meter, theultimate shearing force of 7.61 tons and the limit of deflection of 7.17 mm. Then re-calculated the capacity ofthe existing floor slab in accordance with the Indonesian National Standard (SNI), obtained the internal forcesthat can be borne by the floor slab, namely the slab moment of 18.49 ton.meter, plate shear force of 22.38 tonand the deflection limit. plate by 14.58 mm. So it can be concluded that the floor slab of Pier 005B is capable ofcarrying the Harbor Mobile Crane (HMC) load.